An electrochemical system for the study of trans-plasma membrane electron transport in whole eukaryotic cells - Sherman, Harry G.; Jovanovic, Carolyn; Stolnik, Snow; Rawson, Frankie J. (American Chemical Society, 2018)
The development of new assays to study trans-plasma membrane electron transport (tPMET) in eukaryotic systems is paramount for a number reasons, which include the further understanding of the underlying biology which can then potentially be applied to innovate technological advancements in biosensing, microbial fuel, and pharmaceutical fields. The current literature provides methodology to study these systems that hinges upon mitochondrial knockout genotypes, or the detection of ferrocyanide using colorimetric methods. Developing a method to simultaneously analyze the redox state of a reporter molecule would give advantages in probing the underlying biology. Herein we present an electrochemical based method that allows for the quantification of both ferricyanide and ferrocyanide redox states to a highly sensitive degree. We have applied this system to a novel application of assessing oncogenic cell-driven iron reduction, and have shown that it can effectively quantitate and identify differences in iron reduction capability of three lung epithelial cell lines. Importantly, the development of the technology has led to new biological hypothesis which now need addressing.